TaqMan Probe-Based Quantitative Real-Time PCR to Detect Panax notoginseng in Traditional Chinese Patent Medicines - Lou, Qian; Xin, Tianyi; Xu, Wenjie; Li, Ranjun; Song, Jingyuan (Frontiers in Pharmacology, 2022)
Background: There has been global concern about the safety and accuracy of traditional Chinese patent medicines (TCPMs). Panax notoginseng, also known as sanqi, is an important constituent of TCPMs. However, identifying the species contained in TCPMs is challenging due to the presence of multiple ingredients and the use of various preparation processes. Objective: To detect P. notoginseng in TCPMs. Methods: A TaqMan probe-based qPCR assay was constructed and validated with DNA extracted from P. notoginseng and adulterants. In total, 75 samples derived from 25 batches of TCPMs were tested using the constructed qPCR method. Results: A TaqMan probe-based qPCR assay targeting P. notoginseng was established. The constructed qPCR assay could specifically discriminate P. notoginseng from Panax ginseng, Panax quinquefolium and Curcuma wenyujin. The sensitivity study showed that the detectable DNA template concentration of P. notoginseng for this qPCR assay was 0.001 ng/μL. All 75 samples from TCPMs were confirmed to contain P. notoginseng by the qPCR assay. Conclusions: The qPCR method can accurately identify P. notoginseng in TCPMs and is promising as a powerful tool for quality control and market regulation.